Agama dan Resolusi Konflik dalam Pilkada - Najib, Mohammad (Unisia, 2010)
The article below traces religion and conlict resolution regarding the election ofhead of province or that of regency in Indonesia. The changing of public election system gives an opportunity and chance for people to vote their leader candidates directly. The above situation can emerge some crucial problems, for instance, when candidate proposing by political party, verification the candidate condition, the moment of campaign, the final decision of the elected candidate. In this connection, to prevent and to solve the crucial problems, religion and religious leaders can play important role, for example to keep political ethics, to conduct amar ma’ruf nahi munkar (social control).